The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1074/jbc.273.32.20425
|View full text |Cite
|
Sign up to set email alerts
|

Rab6 Regulation of Rhodopsin Transport inDrosophila

Abstract: Rab6 is a GTPQ71L is a GTPase defective mutant, indicating that anterograde transport of rhodopsin requires Rab6 GTPase function. The three Drab6 strains had no effect on the expression of several other photoreceptor proteins. The Drab6 Q71L photoreceptors show marked histological defects at young ages and degenerate over a two week time span. These results establish that rhodopsin is transported via a Rab6 regulated pathway and that defects in trafficking pathways lead to retinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…It has also been demonstrated that manipulation of Rab6 function through expressing its GTP-bound, GDP-bound or guanidine nucleotide deficient mutants inhibits transport of the plasma membrane proteins hemagglutinin protein and CFTR in mammalian cells and rhodopsin in Drosophila [42,45,46]. Consistent with the role of Rab6 in the plasma membrane targeting, our data indicate that Rab6 is required for the transport to the cell surface of some GPCRs.…”
Section: Discussionsupporting
confidence: 85%
“…It has also been demonstrated that manipulation of Rab6 function through expressing its GTP-bound, GDP-bound or guanidine nucleotide deficient mutants inhibits transport of the plasma membrane proteins hemagglutinin protein and CFTR in mammalian cells and rhodopsin in Drosophila [42,45,46]. Consistent with the role of Rab6 in the plasma membrane targeting, our data indicate that Rab6 is required for the transport to the cell surface of some GPCRs.…”
Section: Discussionsupporting
confidence: 85%
“…This latter aspect of the cnx phenotype most likely reflects an additional role of calnexin as a Ca 2+ buffer [70]. Rab6 also appears to be required for rhodopsin maturation, since expression of a dominant negative form of Rab6 causes defective rhodopsin maturation, and trafficking and triggers retinal degeneration [64]. Taken together, these findings demonstrate that disruption in rhodopsin maturation leads to retinal degeneration.…”
Section: Retinal Degenerationmentioning
confidence: 89%
“…Rab1 is required for rhodopsin transport between the ER and Golgi complex [63], Rab6 functions in the transport through the ER-Golgi complex [64], and Rab11 mediates post-Golgi translocation of rhodopsin [65]. The function of Rab6 may be rhodopsin-specific, whereas Rab1 and Rab11 operate more generally in the trafficking of membrane proteins in photoreceptor cells [63][64][65].…”
Section: Maturation Of Rhodopsinmentioning
confidence: 99%
“…72 Mature Rh1 is transported through the Golgi. The post-Golgi trafficking is orchestrated by monomeric G-proteins including Rab 6 52 and Rab11. 53 Finally, Rh1 is delivered to and inserted into the rhabdomeric membrane.…”
Section: +mentioning
confidence: 99%